Cloning of a cDNA for a major human protein-tyrosine-phosphatase. - Chernoff, J (1990)
We have isolated a cDNA clone encoding the major protein-tyrosine-phosphatase (protein-tyrosine-phosphate phosphohydrolase, EC 3.1.3.48) of human placenta. Degenerate oligonucleotides, based on the amino acid sequence of the protein, were used to amplify an internal fragment of the gene from human placental cDNA by the polymerase chain reaction. This fragment was then used to probe a human placental cDNA library. A 3.3-kilobase (kb) insert was isolated and sequenced. The insert has a single extended open reading frame that predicts a 435 amino acid protein of Mr approximately 50,000. From the amino terminus to residue 321, the deduced amino acid sequence is identical to that previously determined by peptide sequencing [Charbonneau, H., Tonks, N. K., Kumar, S., Diltz, C. D., Harrylock, M., Cool, D. E., Krebs, E. G., Fischer, E. H. & Walsh, K. A. (1989) Proc. Natl. Acad. Sci. USA 86, 5252-5256]; however, the sequence predicts that the protein contains an additional 114 amino acids not present in the reported peptide sequence. In vitro translation of the 3.3-kb insert produces a protein of Mr 56,000, in general agreement with the predicted size. The phosphatase gene appears to be present as a single copy in human genomic DNA and is transcribed into a 3.5-kb message in a variety of tissues.